2021
DOI: 10.1371/journal.pgen.1009664
|View full text |Cite
|
Sign up to set email alerts
|

Increased mitochondrial protein import and cardiolipin remodelling upon early mtUPR

Abstract: Mitochondrial defects can cause a variety of human diseases and protective mechanisms exist to maintain mitochondrial functionality. Imbalances in mitochondrial proteostasis trigger a transcriptional program, termed mitochondrial unfolded protein response (mtUPR). However, the temporal sequence of events in mtUPR is unclear and the consequences on mitochondrial protein import are controversial. Here, we have quantitatively analyzed all main import pathways into mitochondria after different time spans of mtUPR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 57 publications
1
17
0
Order By: Relevance
“…Thus, it is possible that a greater accumulation of misfolded proteins is required to inhibit the mitochondrial import of ATF5 and prompt its nuclear translocation immediately following exercise stress. This is a similar phenomenon to what has been observed in a yeast model, identifying an "early" and "late" UPR mt with diverging efficiencies of mitochondrial protein import depending on the amount of time elapsed post-stress, as well as and the intensity of the stimulus imposed [75]. It is also known that chronically-imposed exercise induces an increase in mitochondrial protein import [76,77].…”
Section: Discussionsupporting
confidence: 80%
“…Thus, it is possible that a greater accumulation of misfolded proteins is required to inhibit the mitochondrial import of ATF5 and prompt its nuclear translocation immediately following exercise stress. This is a similar phenomenon to what has been observed in a yeast model, identifying an "early" and "late" UPR mt with diverging efficiencies of mitochondrial protein import depending on the amount of time elapsed post-stress, as well as and the intensity of the stimulus imposed [75]. It is also known that chronically-imposed exercise induces an increase in mitochondrial protein import [76,77].…”
Section: Discussionsupporting
confidence: 80%
“…Increased levels of TOMM22 may enhance formation of the TOM complex and facilitate protein import into mitochondria to partially alleviate the mitochondrial damage induced by TMEM160 depletion. Indeed, a recent study reported that mitochondrial protein import is enhanced at an early stage of the UPR mt [26]. Thus, TMEM160 depletion may result in important but not strong upregulation of the UPR mt and TOMM22 to prevent mitochondrial damage.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, pterostilbene in combination with mitochondrial cofactors treatment activates SIRT3 and UPR mt as compensatory mechanisms as well as enhance sirtuins' levels and mitochondrial activity in several cell models of mitochondrial diseases. Recent findings have led to an increase in the relevance of UPR mt activation as a novel therapeutic approach for the treatment of mitochondrial diseases and related conditions (Poveda-Huertes et al, 2021) (Ji et al, 2020). Interestingly, this potent compensatory pathway may not be active in cells bearing a range of different mutations that secondarily affect mitochondrial proteostasis (Pitera et al, 2019).…”
Section: Discussionmentioning
confidence: 99%